A tuft cell-like signature is highly prevalent in thymic squamous cell carcinoma and delineates new molecular subsets among the major lung cancer histotypes - Yamada, Yosuke; Simon-Keller, Katja; Belharazem, Djeda; Bohnenberger, Hanibal; Kriegsmann, Mark; Kriegsmann, Katharina; Hamilton, Gerhard; Graeter, Thomas; Preissler, Gerhard; Ott, German; Roessner, Eric Dominic; Dahmen, Ilona; et al. (Journal of thoracic oncology, 2021)
Introduction - In-depth genomic characterization of thymic epithelial tumors (TETs), comprising thymomas and thymic carcinomas (TCs), failed to identify targetable mutations and suggested unique biology of TETs, including KIT expression in most TCs. Recently, tuft cell-like medullary thymic epithelial cells were identified in the murine thymus, and our reanalysis of the published gene expression data revealed that these cells express KIT. In addition, recently, a minor subset of SCLCs with tuft cell-like features was described. - Methods - We interrogated mRNA expression data from our tumor cohorts (N = 60) and publicly available, independent data sets from TETs and NSCLC (N = 1199) for expression of tuft cell genes and KIT. Expression of KIT and of POU2F3 protein, the master regulator of tuft cells, was analyzed in cancer tissue (N = 344) by immunohistochemistry. - Results - Normal human thymic tuft cells and most TCs coexpressed KIT and known tuft cell genes, particularly POU2F3 and GFI1B. Unexpectedly, small subsets of tuft cell-like tumors coexpressing POU2F3, GFI1B, and KIT were also identified among pulmonary squamous cell carcinomas, adenocarcinomas, and large cell neuroendocrine carcinoma and clustered together in each histologic cohort. In addition to the tuft cell-like signature, both thymic and lung tuft cell-like carcinomas had distinct genetic, pathologic, and clinical features in each cohort. - Conclusions - We suggest that the tuft cell-like phenotype defines novel subsets of thymic and pulmonary carcinoma. Its high prevalence in thymic squamous cell carcinomas that have no known toxic or viral etiologies suggests a new mechanism of carcinogenesis that may lead to specific drug susceptibilities.